Student-centred cloze: a new tool for measuring EFL reading comprehension - Karim Sadeghi, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Cloze procedure, originally intended for a totally different purpose, is one of the measurement tools widely used and experimented upon by testing scholars in the field of EFL/ESL. Based on correlational studies between cloze test results and those of others mainly including language proficiency and reading comprehension, and motivated by the simplicity with which cloze tests are constructed, administered and scored, such tests have so conveniently been proposed to replace reading or proficiency tests. The history of cloze testing has also seen various versions from Taylor’s (1953) original version (often termed standard, regular or classical) to numerous sorts of rational cloze. This study introduces a new cloze version, termed student-centred cloze and reports the findings of a quantitative study on such a cloze as a measure of EFL reading comprehension as measured by FCE and CAE Reading Papers with 53 Iranian EFL learners. While correlational validation confirms student-centred cloze as a valid measure of reading comprehension, arguments are made against such correlational validation at the end of the paper